2016
DOI: 10.3168/jds.2015-9487
|View full text |Cite
|
Sign up to set email alerts
|

Udder infections with Staphylococcus aureus, Streptococcus dysgalactiae, and Streptococcus uberis at calving in dairy herds with suboptimal udder health

Abstract: Udder infections with Staphylococcus aureus, Streptococcus dysgalactiae, and Streptococcus uberis are common causes of bovine mastitis. To study these pathogens in early lactation, a 12-mo longitudinal, observational study was carried out in 13 herds with suboptimal udder health. The aims of the study were to investigate the occurrence of these pathogens and to identify if presence of the 3 pathogens, and of genotypes within the pathogens, differed with respect to herd, season, and parity. Quarter milk samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 46 publications
(49 reference statements)
2
32
0
3
Order By: Relevance
“…The abundance of Staphylococcus in manure was higher than that in fresh feces and soil, the most important member of this genus being S. aureus . S. aureus is still described as one of the most frequently isolated etiological agents associated with bovine intramammary infections [51, 52], and some studies have shown a high incidence of S. aureus with genomic variation in resistance genes, which may pose a threat to public and animal health in Ningxia Province, China [53]. These pathogens displayed differences in antimicrobial resistance and could serve as carriers introducing antibiotic resistance genes into the food chain.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of Staphylococcus in manure was higher than that in fresh feces and soil, the most important member of this genus being S. aureus . S. aureus is still described as one of the most frequently isolated etiological agents associated with bovine intramammary infections [51, 52], and some studies have shown a high incidence of S. aureus with genomic variation in resistance genes, which may pose a threat to public and animal health in Ningxia Province, China [53]. These pathogens displayed differences in antimicrobial resistance and could serve as carriers introducing antibiotic resistance genes into the food chain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this method is characterized by high resolution and is associated with the virulence gene pattern of bovine strains (Fournier et al, 2008;Graber et al, 2009;Cremonesi et al, 2015;. Besides RS-PCR, other subtyping methods have been used to further characterize staphylococcal IMI isolates such as spa typing (e.g., Boss et al, 2016;Lundberg et al, 2016), multilocus sequence typing (e.g., Hata et al, 2010;Boss et al, 2016), pulsed-field gel electrophoresis (e.g., Capurro et al, 2010;Cremonesi et al, 2015), and amplified fragment length polymorphism (Sakwinska et al, 2011). Their suitability for large clinical investigations, however, is mainly limited by low throughput or high cost.…”
Section: Introductionmentioning
confidence: 99%
“…Influences from breed, age and lactation stage of the animal have been described (Haftu et al ; Oliveira et al ). Staphylococcus aureus is one of the most important bacterial pathogens causing bovine mastitis (Tenhagen et al ; Wang et al ; Lundberg et al ; Srednik et al ). Mastitis caused by this bacterium has a lower cure rate than for most of the other bacteria (Sartori et al ; Srednik et al ).…”
Section: Introductionmentioning
confidence: 99%